2016
DOI: 10.1111/jce.13024
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Study of Left and Right Atria in Isolated Rheumatic Mitral Stenosis With and Without Atrial Fibrillation

Abstract: In rheumatic MS, SR is associated with myocyte hypertrophy whereas AF is associated with myocytolysis. Endocardial inflammation is more common in left atrial appendage irrespective of rhythm. Interstitial fibrosis is seen in >90% of patients distributed in both the atria and is independent of the rhythm. Amyloid and Aschoff bodies are uncommon and the rest of the changes are uniformly distributed across both the atria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…18 Myocyte hypertrophy was the most common histological finding in our study; however, glycogen deposits were not seen. We also noted the severity of the myocyte hypertrophy being more on the right than the left side of the heart, which is a unique finding not seen in our previous study in patients with isolated MS 7 and warrants additional evaluation in a bigger sample size for an explanation.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…18 Myocyte hypertrophy was the most common histological finding in our study; however, glycogen deposits were not seen. We also noted the severity of the myocyte hypertrophy being more on the right than the left side of the heart, which is a unique finding not seen in our previous study in patients with isolated MS 7 and warrants additional evaluation in a bigger sample size for an explanation.…”
Section: Discussionsupporting
confidence: 59%
“…The details of the operative procedure have been described before. 7 The surgeons (Ravikumar N. Kalyani and Giridhar Kamalapurkar) performed the surgery through a standard median sternotomy under general anesthesia, aortobicaval cannulation, cardiopulmonary bypass, systemic heparinization, and moderate hypothermia, and cold sanguineous hyperkalemic cardioplegia. Through a paraseptal incision left atrium (LA) was opened.…”
Section: Operative Procedures and Procurement Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bois et al 10 in their study of 149 consecutive patients with AF, found that DGE within LA walls was uncommon and when present, did not correlate with AF type or risk of AF recurrence. Shenthar et al 11 conducted histological studies of left and right atria in rheumatic MS. They found that sinus rhythm was associated with myocyte hypertrophy whereas AF was associated with myocytolysis.…”
Section: Discussionmentioning
confidence: 99%